2021
DOI: 10.1017/s0954579421001176
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity and depressive symptoms among early adolescent girls: the mediating role of exposure to recent interpersonal acute stress

Abstract: Early adversity confers risk for depression in part through its association with recent (i.e., proximal) acute stress. However, it remains unresolved whether: a) early adversity predicts increases in recent acute stress over time; b) all – or only certain types – of recent events mediate the relationship between early adversity and depression; and c) early adversity places individuals at greater risk for depression via greater exposure to independent (i.e., fateful) interpersonal events or via greater generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…These interpersonal problems may in turn lead to more mental health problems, including depressive symptoms (Cheek et al, 2020;He et al, 2019). In the only study focusing on the mediating role of interpersonal stress in the relationship between early adversities and depressive symptoms, Stroud et al (2021) found that early adversity may not be directly related to subsequent depressive symptoms, but past-year acute interpersonal stress was a significant mediator. Similarly, we found that childhood trauma was associated with interpersonal stress and that interpersonal stress also mediated the relationship between childhood betrayal trauma and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These interpersonal problems may in turn lead to more mental health problems, including depressive symptoms (Cheek et al, 2020;He et al, 2019). In the only study focusing on the mediating role of interpersonal stress in the relationship between early adversities and depressive symptoms, Stroud et al (2021) found that early adversity may not be directly related to subsequent depressive symptoms, but past-year acute interpersonal stress was a significant mediator. Similarly, we found that childhood trauma was associated with interpersonal stress and that interpersonal stress also mediated the relationship between childhood betrayal trauma and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Third, future research should evaluate whether exposure to recent stress affects the relationship between the dimensions of early adversity and LTC. Importantly, research supporting stress continuity suggests that individuals who face early adversity experience higher levels of stress across development (in comparison to those who do not experience early adversity; e.g., Korkeila et al., 2010), particularly interpersonal and independent forms of acute stress (Stroud et al., 2021). The accumulation of such forms of acute stress has also evinced links with LTC, over and above the effect of early adversity (Stroud et al., 2016b).…”
Section: Discussionmentioning
confidence: 99%